1999
DOI: 10.1016/s1388-9842(98)00007-5
|View full text |Cite
|
Sign up to set email alerts
|

The WASH study (Warfarin/Aspirin Study in Heart failure) rationale, design and end‐points

Abstract: Background: Athero-thrombotic events are common among patients with heart failure but there is no evidence that anti-thrombotic therapy is safe or effective in this clinical setting. Aims and Methods: The WASH study is a prospective, randomised, open-label, blinded-end-point pilot study comparing the outcome of management without anti-thrombotic therapy compared to treatment with aspirin or warfarin in three parallel arms in patients with chronic heart failure due to left ventricular systolic dysfunction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 18 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Contrary to the prior findings, the Warfarin/Aspirin Study in Heart Failure (WASH) found that there was no evidence of aspirin being safe or effective in patients with heart failure. The study also could not demonstrate the benefit of the use of warfarin for patients with HFrEf with sinus rhythm [ 13 ]. Heart failure Long-Term antithrombotic study (HELAS) was a randomized, placebo-controlled trial to demonstrate the effect of long-term antithrombotic therapy in patients with chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the prior findings, the Warfarin/Aspirin Study in Heart Failure (WASH) found that there was no evidence of aspirin being safe or effective in patients with heart failure. The study also could not demonstrate the benefit of the use of warfarin for patients with HFrEf with sinus rhythm [ 13 ]. Heart failure Long-Term antithrombotic study (HELAS) was a randomized, placebo-controlled trial to demonstrate the effect of long-term antithrombotic therapy in patients with chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%